INSTITUSI DAN SISTEM PENDIDIKAN ISLAM. SUATU ANALISA TAHAP PERKEMBANGANNYA DI KELANTAN - Yusuff, Nur Azuki; Nik Abdullah, Nik Kamaliah (Journal of Al-Tamaddun, 2007)
The state of Kelantan historically has been well known for its Islamic institutions especially pertaining institutions of Islamic education since the advent of Islam till present. This article will discuss in detail the growth of Islamic educational system and institution in Kelantan since pre-independent and after which can be divided into several stages. Historical and documentation methods are applied in collecting the data in present article. Research findings show that the growth of Islamic educational system and institution in Kelantan is divided in to six stages that will be discussed in detail here.